Architecture of the ring formed by the tubulin homologue FtsZ in bacterial cell division - Szwedziak, Piotr (eLife, 2014)
Membrane constriction is a prerequisite for cell division. The most common membrane constriction system in prokaryotes is based on the tubulin homologue FtsZ, whose filaments in E. coli are anchored to the membrane by FtsA and enable the formation of the Z-ring and divisome. The precise architecture of the FtsZ ring has remained enigmatic. In this study, we report three-dimensional arrangements of FtsZ and FtsA filaments in C. crescentus and E. coli cells and inside constricting liposomes by means of electron cryomicroscopy and cryotomography. In vivo and in vitro, the Z-ring is composed of a small, single-layered band of filaments parallel to the membrane, creating a continuous ring through lateral filament contacts. Visualisation of the in vitro reconstituted constrictions as well as a complete tracing of the helical paths of the filaments with a molecular model favour a mechanism of FtsZ-based membrane constriction that is likely to be accompanied by filament sliding. DOI: http://dx.doi.org/10.7554/eLife.04601.001